A Study on the Model of Animation Style Using PCAF - Riwinoto Riwinoto; Arifatul Hidayah (Politeknik Negeri Batam, 2020)
Stylized, snappy, and limited animations are three popular movements of animation nowadays. The objective parameters of this style never conducted previously. The researcher proposed a technique named Principle Contained Animated in Frame (PCAF) to obtain the model of animation style. The technique is basically taking information on how often the motion follows the 12 principles of animation. This study begins sampling for all of animated film styles where each style has three examples of films. After getting a percentage of each PCAF on principles of animation, some steps were conducted to find a model. Important steps are unelimination, ascending elimination and final position adjustment. The results of the study at the latest stage showed that the principles of animation numbers 7,3,2,9,10,12 and 16 are the principles formed the special features which are shown in the pattern of stylized animation style, while numbers 4,10,12,2,9,1,6,7 and 3 formed the special features shown in the pattern of snappy animation syle and on the pattern of limited animation style, the principles of which indicated special features form of this style are 2,3,6,11,9 and 12